2016
DOI: 10.1177/0146167216642196
|View full text |Cite
|
Sign up to set email alerts
|

Living in a Genetic World

Abstract: Information about the degree of one's genetic overlap with ethnic outgroups has been emphasized in genocides, is frequently learned about through media reporting, and is increasingly being accessed via personal genetic testing services. However, the consequence of learning about whether your own ethnic group is either genetically related to or genetically distinct from a disliked ethnic group remains unknown. Across four experiments, using diverse samples, measures and contexts, we demonstrate that altering pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 57 publications
1
20
0
Order By: Relevance
“…Gender did not moderate the effects (0.105 < ps < 0.138). As the killed and slaughtered conditions did not differ from each other (p ¼ 0.769), both were merged and compared to the harvest condition in consecutive analyses similar to analytic procedures in previous research (Kimel, Huesmann, Kunst, & Halperin, 2016;Kunst, Thomsen, Sam, & Berry, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Gender did not moderate the effects (0.105 < ps < 0.138). As the killed and slaughtered conditions did not differ from each other (p ¼ 0.769), both were merged and compared to the harvest condition in consecutive analyses similar to analytic procedures in previous research (Kimel, Huesmann, Kunst, & Halperin, 2016;Kunst, Thomsen, Sam, & Berry, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…A 9-item scale (α = .95) developed by Vail and Motyl (2010) and adapted to the Israeli-Palestinian conflict by Kimel et al (2016) measured support for Israeli-Palestinian peacemaking. The scale measured the extent to which participants believed that Israel should pursue diplomatic negotiations with the Palestinians CAN ABRAHAM BRING PEACE?…”
Section: Support For Israeli-palestinian Peacemakingmentioning
confidence: 99%
“…rooted in theological issues. Indeed, the current work only addresses one component of a very complex and multifaceted conflict and, thus, our approach may be most useful in combination with other promising approaches such as emphasizing common victimhood and loss (Gayer, Landman, Halperin, & Bar-Tal, 2009;Shnabel, Halabi, & Noor, 2013), stressing emotional similarities (McDonald et al, 2015), nurturing positive emotions such as hope and empathy (Rosler et al, 2015), satisfying the different conflict parts' specific social needs Shnabel & Nadler, 2008;Shnabel, Nadler, Ullrich, Dovidio, & Carmi, 2009), emphasizing intergroup genetic similarity (Kimel et al, 2016), cognitive reappraisals (Halperin et al, 2014), third-party mediation (Schrodt & Gerner, 2004) or contact workshops (Malhotra & Liyanage, 2005;Shani & Boehnke, in press). Future research may benefit from comparing the strength of Abrahamic categorization to these other conflict reduction approaches and also test its effects in combination with them.…”
Section: Future Research and Societal Implicationsmentioning
confidence: 99%
“…The few studies seeking to adjudicate between these outcomes have focused on the effect of reading media articles about GATs and found that reading articles depicting the tests as able to reveal a person's race, or emphasizing the degree of overall genetic difference between groups, increases belief in essential racial and ethnic differences [17,32,33]. However, the media articles in these studies included clear statements supporting or opposing a genetic basis to race; by contrast, the experience of taking a GAT requires the test-taker to actively interpret complex, personalized results.…”
Section: Introductionmentioning
confidence: 99%